ANALISIS MANAJEMEN RISIKO KREDIT SEBAGAI ALAT UNTUK MEMINIMALISIR RISIKO KREDIT (Studi pada PT. Bank Rakyat Indonesia (PERSERO) Tbk. Cabang Malang Kawi) - Fairuza, Denes Ahmad; Champaca, Mychelia (Jurnal Ilmiah Mahasiswa FEB, 2013)
A bank has a very vital role for the economy of a country. Indonesian banks currently face a new challenge that is to increase preparedness in the face of the global crisis, in which the global crisis will take a lot of risk for banks in Indonesia. One of them is credit risk. Especially the credit risk is the risk that most often affects banks in Indonesia with the greatest impact. This study aims to determine the application of risk management in PT BRI Kanca Malang Kawi as a tool to minimize credit risk. The next goal is to find out the effectiveness of risk management in minimizing credit risk. Results of this study indicate that the credit risk management of PT BRI Kanca Malang Kawi performed by stage of identification of credit risk factors, measurement and managing and controlling credit risk. In addition, the application of risk management PT BRI Kanca Malang Kawi has been effective in minimizing credit risk. Keyword : Bank Risk, Credit Risk, and Credit Risk Management